ANTIOXIDANT AND ANTICANCER POTENTIALS OF BIOFABRICATED SILVER NANOPARTICLES - Paul Das, Merina; Rebecca, L Jeyanthi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of this study is to explore a rapid, bio-inspired approach to synthesize silver nanoparticles (AgNPs) using aqueous Nardostachys jatamansi leaf extract and evaluate its antioxidant and cytotoxic activities on human colon carcinoma (HCT-116) cell lines. Methods: The biosynthesized nanoparticles were analyzed using ultraviolet-visible spectrophotometer, scanning electron microscope (SEM), energy dispersive X-ray, X-ray diffractometer (XRD), and Fourier transform infrared spectroscopy. Free radical scavenging and cytotoxic studies were carried out at different concentrations of AgNPs (20-100 Î¼g/mL) using antioxidant 2,2-diphenyl-1-picrylhydrazil (DPPH) and mitochondrial function assay methods. Results: Surface plasmon resonance spectrum at 434 nm confirmed the formation of AgNPs. SEM images show biosynthesized AgNPs are mostly spherical shaped within the range of 30.0-58.7 nm. XRD analysis reveals the crystallographic face-centered cubic structure of the AgNPs. Thus, synthesized metal nanoparticles were tested for antioxidant activity by DPPH assay, and anticancer activity was validated by lactate dehydrogenase leakage assay. Significant antioxidant property was observed as compared to standard L-ascorbic acid. Further, AgNPs showed a linear dose-response relationship against HCT-116 cell lines with increasing concentration of AgNPs. At a concentration of 20 Î¼g/mL, AgNPs were able to inhibit the cell line's growth by less than 9.8 Â± 0.7%, whereas 100 Î¼g/mL of AgNPs significantly inhibited the cell line's growth greater than 90.4 Â± 0.25%. Conclusion: The synthesized AgNPs were found to be highly stable and had significant antioxidant and anticancer activity against HCT-116 cell lines. It has wide applications in the biomedical field and can be produced with eco-friendly, rapid scale-up, and easy downstream processing.